2015
DOI: 10.1007/s10639-015-9402-8
|View full text |Cite
|
Sign up to set email alerts
|

Virtual schools: The changing landscape of K-12 education in the U.S.

Abstract: Virtual schools are a growing phenomenon in k-12 education. School systems in almost every state in the United States offer some version of fully online or blended education. It is no longer far-fetched to conclude that if the current trend continues, virtual school enrollments will eclipse those of traditional brick-and-mortar k-12 institutions within the next 10 years. This paper examines some of the challenges and strengths of virtual schools, it offers questions to consider when deciding whether or not a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…Distance education is now a solution not only in compulsory situations such as the pandemic lockdown but also as a support to facilitate education processes in both face-to-face and virtual education settings to reach students wherever they are. For this reason, different distance education applications, including virtual schools (Toppin & Toppin, 2016), online learning environments (Arnesen et al, 2019;Berge & Clark, 2005) and e-content (Mishra et al, 2017), have gained in importance and popularity. As a result of these innovations, online learning environments, which offer web-based education or training over the Internet, have been widely used in K-12 education in many countries.…”
Section: Theoretical Background: Implementations Of Distance Education In K-12 Schools Around the Worldmentioning
confidence: 99%
“…Distance education is now a solution not only in compulsory situations such as the pandemic lockdown but also as a support to facilitate education processes in both face-to-face and virtual education settings to reach students wherever they are. For this reason, different distance education applications, including virtual schools (Toppin & Toppin, 2016), online learning environments (Arnesen et al, 2019;Berge & Clark, 2005) and e-content (Mishra et al, 2017), have gained in importance and popularity. As a result of these innovations, online learning environments, which offer web-based education or training over the Internet, have been widely used in K-12 education in many countries.…”
Section: Theoretical Background: Implementations Of Distance Education In K-12 Schools Around the Worldmentioning
confidence: 99%
“…Additionally, however, we found that credit recovery students occurred in the high‐quantity profile at more than a chance level. Toppin and Toppin () stated that “virtual schooling can be an effective tool for providing failing or at‐risk students with additional remediation instruction and materials, apart from regular instruction, and verifying whether or not they are accessing those materials regularly and effectively” (p. 1578). We postulate that the novelty of the online learning experience may explain the high levels of autonomous motivation that we observed, through its reshaping of credit recovery students' enjoyment of and curiosity about their courses; while at the same time, ongoing pressure to pass could account for our findings of high levels of controlled motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of VSs know there are several advantages VS students at the secondary level receive that their traditionally-schooled counterparts may not. Virtual schooling affords students the opportunity to learn at times and places that are suitable for them (Kirby et al 2010;Lewis, Whiteside, and Dikkers 2014;Morgan 2015;Oliver, Osborne, and Brady 2009;Pastore and Carr-Chellman 2009;Roblyer 1999;Russell 2006;Strader et al 2015;Toppin and Toppin 2016;Wang and Decker 2014). This is a major advantage for those students who, like many teenagers, do not like the school hours that traditional schools maintain.…”
Section: Advantages Of Virtual Schoolsmentioning
confidence: 99%
“…In addition to the ability to work at various times from various places, students can also work at their own pace (Borup, Graham, and Davies 2013;Lewis, Whiteside, and Dikkers 2014;Morgan 2015;Oliver, Osborne, and Brady 2009;Toppin and Toppin 2016). For those students looking for classes that may not be offered at their traditional high schools, VSs often offer many courses that cannot be or are not offered at traditional schools for various reasons such as financial or personnel limitations (Oliver, Osborne, and Brady 2009;Toppin and Toppin 2016). Virtual schools also afford learners greater personalized instruction and support from their teachers (Oliver, Osborne, and Brady 2009).…”
Section: Advantages Of Virtual Schoolsmentioning
confidence: 99%